Determinants of Indonesia’s Coffee Commodity with Trading Partner Countries - Deassy Apriani; Feny Marissa; G Gustriani; Harta Sinta (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2022)
This study measures the Intra Industry Trade Index / Rubel Lloyd Index of Indonesia’s coffee commodities with trading partner countries (Singapore, Malaysia, Thailand, Vietnam and Philippines) and estimates factors the influence of Intra Industry Trade of Indonesia’s coffee commodities. The presented data is obtained from secondary data with the research period from 2000 to 2019 using panel data analysis to know the extent influence of the independent variables (average GDP, GDP value differences per capita, exchange rates and distance) on the dependent variable (Intra-Industry Trade). Based on the estimation results, it can be concluded that the integration degree of intra-industry trade for Indonesian coffee commodities with trading partner countries has varying degrees. This indicates that there is a dependence on the coffee commodity trade. The availability of coffee commodities in these countries is highly dependent on intra-industry exports and imports value between Indonesia and its trading partner countries.